2017
DOI: 10.3389/fcimb.2017.00073
|View full text |Cite
|
Sign up to set email alerts
|

Tick Thioester-Containing Proteins and Phagocytosis Do Not Affect Transmission of Borrelia afzelii from the Competent Vector Ixodes ricinus

Abstract: The present concept of the transmission of Lyme disease from Borrelia-infected Ixodes sp. ticks to the naïve host assumes that a low number of spirochetes that manage to penetrate the midgut epithelium migrate through the hemocoel to the salivary glands and subsequently infect the host with the aid of immunomodulatory compounds present in tick saliva. Therefore, humoral and/or cellular immune reactions within the tick hemocoel may play an important role in tick competence to act as a vector for borreliosis. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
(107 reference statements)
3
23
0
Order By: Relevance
“…Instead, we assume that regurgitation, or rather active reverse migration of motile spirochetes from midgut to the mouthpart (for which we coin the term ‘gut-to-mouth’ route) is the most probable way of transmission of B. afzelii from I. ricinus nymph to the host. This alternative way of B. afzelii transmission avoiding I. ricinus hemocoel and salivary glands is indirectly supported also by our recent research showing that silencing of tick immune molecules or elimination of phagocytosis in tick hemocoel by injection of latex beads had no obvious impact on B. afzelii transmission (3335).…”
Section: Discussionsupporting
confidence: 57%
“…Instead, we assume that regurgitation, or rather active reverse migration of motile spirochetes from midgut to the mouthpart (for which we coin the term ‘gut-to-mouth’ route) is the most probable way of transmission of B. afzelii from I. ricinus nymph to the host. This alternative way of B. afzelii transmission avoiding I. ricinus hemocoel and salivary glands is indirectly supported also by our recent research showing that silencing of tick immune molecules or elimination of phagocytosis in tick hemocoel by injection of latex beads had no obvious impact on B. afzelii transmission (3335).…”
Section: Discussionsupporting
confidence: 57%
“…By using the tick hemocytes of semi-engorged females we tested the effects of individual ixoderin KDs on the phagocytosis of B. afzelii CB43. For this purpose we used a phagocytic assay (modified from Urbanova et al, 2017 ) that can reliably distinguish between spirochetes located outside of the hemocytes, sticking to their surface, and those, which were certainly phagocytosed (Figure 6 ). The phagocytosis of Borrelia can be reduced by pre-incubation of the hemolymph with the thioester-blocking reagent methylamine (Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the tick salivary protein TSLPI inhibits the host complement system and thus facilitates Borrelia transmission (Schuijt et al, 2011a , b ). By using the Borrelia -phagocytic assay and Borrelia -transmission system (Urbanova et al, 2017 ) we tested whether tick ixoderins, expressed both in the hemolymph and salivary glands, are able to activate the tick complement-like system and kill the spirochetes or bind to the surface of pathogens to protect them in the tick vector or the vertebrate host. In these assays we used in vitro cultivated Borrelia (BSK-H complete medium, 33°C), which express similar surface proteins as the activated spirochetes in the tick hemolymph during tick feeding and are infectious to the vertebrate host (Obonyo et al, 1999 ; Ohnishi et al, 2001 ; Dunham-Ems et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…possess a number of immune effectors and modulators such as recognition molecules, among them thioester-containing proteins (T-TEPS, that serve as lectins labeling cells for immune attack), phagocytotic hemocytes, defensins, lysozymes, antimicrobial peptides, a dityrosine network (DTN), and (atypical) signaling pathways. The signaling pathways regulating the immune system include Toll, IMD (Immunodeficiency) and JAK-STAT (Janus Kinase/Signal Transducers and Activators of Transcription) as well as an indirect, cross-species signaling pathway that recognizes the cytokine interferon gamma in the blood of the vertebrate host (Johns et al, 2001;Hajdusek et al, 2013;Yang et al, 2014;Sonenshine and Macaluso, 2017;Urbanova et al, 2017). RNA interference studies on genes involved in the tick's immune response have shown that depletion of expression may lead to suppression of Borrelia colonization in ticks (Narasimhan et al, 2017) suggesting that Borrelia can exploit tick molecules to its own advantage.…”
Section: Tick Immunitymentioning
confidence: 99%